Determination of Antibacterial Efficacy of Different Soaps Found in the Local Market against Common Pathogenic Bacteria (Tribhuvan University Journal of Microbiology, 2025)
Objective:  This study aimed to evaluate the antibacterial efficacy of different type of soaps against Staphylococcus aureus, Escherichia coli and Bacillus species.Methods: A laboratory-based experimental study was conducted from February 2024 to July 2024. Eight commonly used soaps (Herbal, Non-medicated, Medicated, Liquid and Laundry) were randomly collected from the local market of Kathmandu valley. The bacterial cultures used for test were standardized to 0.5McFarland. The soap solutions were prepared by dissolving each soap in sterile distilled water (100mg/ml), and two-fold dilution made for MIC testing. Antibacterial activity was assessed by Agar Well Diffusion method using Mueller-Hinton Agar. Wells were filled with 1ml of each prepared soap solution and incubated at 37°C for 24 hours. Zones of Inhibition were measured, and MIC was determined as the lowest dilution showing no visible growth.Results: Non-medicated soaps showed mean ZOI of 16.7mm (NM1 brand being effective with mean ZOI of 21 mm) and medicated soap showed mean ZOI of 16.1mm. Handwash showed ZOI range between 16-19mm with mean of 17.3mm. Herbal soap has a strong 17mm of mean ZOI with range of 8-23mm. The brand NM1 soap showed most effective against E. coli (20mm) and least against S. aureus (15mm) with MIC value 1.56mg/ml. Herbal soap showed maximum effect against E. coli (20mm) with MIC value 6.25mg/ml and of 3.125mg/ml against S. aureus. Other soaps showed MIC in the range from 3.125mg/ml to 50mg/ml.Conclusion: Non-medicated soap showed the strongest antibacterial activity against Bacillus and E. coli, while Herbal soap was most effective against S. aureus. Difference in efficacy among soaps are attributed to variation in their antimicrobial compound. The finding challenges the idea that medicated soaps are always more effective than non-medicated ones. Soap formulation should prioritize proven antimicrobial efficacy while remaining affordable for widespread use.